(untitled) (Comprehensive Journal of Science, 2026)
This study examines the asymmetric impact of money supply dynamics on economic stability in Libya (1990-2020) using the Nonlinear Autoregressive Distributed Lag (NARDL) approach. To ensure methodological consistency, the exchange rate of the Libyan Dinar is utilized as a proxy for economic stability. Results confirm a nonlinear cointegrating relationship, highlighting a significant "asymmetry" in the long run. Specifically, monetary contraction (negative shocks) exerts a more potent and statistically significant effect on the exchange rate compared to monetary expansion (positive shocks), indicating price stickiness and downward rigidity in the Libyan market. The study recommends implementing flexible monetary frameworks and enhancing fiscal-monetary coordination to mitigate the disproportionate effects of liquidity shocks on currency stability.